Exchange Bias Effect in Epitaxial LaMnO3+δ Film Induced by Electron Beam Irradiation. Issue 2 (10th December 2019) - Xue, Mingzhu; Ding, Shilei; Lai, Youfang; Li, Xin; Zha, Liang; Peng, Yuxuan; Liang, Zhongyu; Yang, Wenyun; Men, Yong; Kong, Xiangdong; Han, Li; Chen, Xuegang; et al.
Abstract: Phase separation in the perovskite manganites of R1‐ x A x MnO3 (R = trivalent lanthanide cation and A = divalent alkaline‐earth cation) can induce novel phenomena associated with the interfacial interactions. Here, the occurrence of phase separation and unexpected exchange bias induced by electron beam irradiation (EBI) in the epitaxial LaMnO3+δ (LMO) thin films is reported. The transformation from Mn 4+ ion to Mn 3+ ion originating from the electron's reducibility, enhances the Mn 3+ –Mn 3+ antiferromagnetic superexchange interaction, resulting in phase separation, namely, the coexistence of ferromagnetic matrix and antiferromagnetic clusters. The formation of the antiferromagnetic phase in the LMO film is closely related to the increase of the out‐of‐plane lattice constant and the decrease of Curie temperature after EBI. The unexpected exchange bias effect results from the interfacial interaction between the ferromagnetic matrix and antiferromagnetic clusters, triggered by EBI in LMO film. The discovery of exchange bias induced by EBI shed promising light on achieving the tunable exchange bias effect in spintronic devices for single‐phase films. Abstract : Electron beam irradiation (EBI) is a feasible way to control the oxygen content in the perovskite manganites. It is reported that the decrease of oxygen content in LaMnO3+δ film after EBI processing, results in the coexistence of antiferromagnetic clusters and ferromagnetic matrix. The exchange bias effect emerges due to the interfacial interaction at the boundaries of two phases.